Pelvic Venous Congestion Secondary to a Circumaortic Renal Collar in an Adolescent Female: Report of a Case - Verónica Alonso-Arroyo; Jose Javier Velasco; Sonia Pérez-Bertólez; Maria Elena Molina; Jose Manuel Marugan-; Alberto Sanchez-Abuin; Oscar Dario Gomez Beltran (Georg Thieme Verlag KG, 2021)
We report a 13-year-old girl who presented with a recurrent abdominal pain that started after her menarche. The abdominal palpation revealed tenderness over the left ovarian point. The laboratory study, ultrasonography, and abdominal X-ray were normal. The computed tomography and magnetic resonance imaging showed a double left renal vein with a retroaortic component, an increased left parauterine circulation, and ipsilateral ovarian vein engorgement. A diagnostic and therapeutic phlebography allowed a selective catheterization of a group of pelvic varicose veins draining to the left ovarian and to the internal iliac veins. There were no complications during the procedure and the symptoms disappeared 2 days later. Circumaortic left renal vein may cause hematuria, proteinuria, pelvic congestion syndrome, and massive hemorrhage during surgery. A conservative treatment is recommended for patients without gynecourological/renal symptoms or with mild hematuria. The endovascular treatment by gonadal venous embolization is safe and effective.